Sustained delivery of chABC improves functional recovery after a spine injury - Atousa Sharifi; Ali Zandieh; Zahra Behroozi; Michael R. Hamblin; Sara Mayahi; Mahmoud Yousefifard; Fatemeh Ramezani (BMC Neuroscience, 2022)
Abstract Introduction Chondroitinase ABC (chABC) is an enzyme could improve regeneration and thereby improving functional recovery of spinal cord injury (SCI) in rodent models. Degradation of the active enzyme and diffusion away from the lesion are the causes of using hydrogels as a scaffold to deliver the chABC into the lesion site. In this meta-analysis, we investigated the effects of chABC embedded in a scaffold or hydrogel on the functional recovery after SCI. Method Databases were searched based on keywords related to chABC and spinal cord injury (SCI). Primary and secondary screening was performed to narrow down study objectives and inclusion criteria, and finally the data were included in the meta-analysis. The standard mean difference of the score of the functional recovery that measured by Basso, Beattie, Bresnahan (BBB) test after SCI was used to analyze the results of the reported studies. Subgroup analysis was performed based on SCI model, severity of SCI, transplantation type, and the follow-up time. Quality control of articles was also specified. Results The results showed that embedding chABC within the scaffold increased significantly the efficiency of functional recovery after SCI in animal models (SMD = 1.95; 95% CI 0.71–3.2; p = 0.002) in 9 studies. SCI model, severity of SCI, injury location, transplantation type, and the follow-up time did not affect the overall results and in all cases scaffold effect could not be ignored. However, due to the small number of studies, this result is not conclusive and more studies are needed. Conclusion The results could pave the way for the use of chABC embedded in the scaffold for the treatment of SCI and show that this method of administration is superior to chABC injection alone.